Speeches to No One: On the Effectiveness of Russian Ressentiment Criticism - Fishman; L.G. (Дискурс Пи, 2022)
The article is aimed at analyzing the effectiveness of the strategy of Russian ressentiment criticism. It characterizes the concept of ressentiment as a tool of denunciation, re-education, and social criticism. The author argues that the classical and modern criticism of ressentiment is a criticism of "false consciousness" from the right. It boils down to discrediting any attempts of the "humiliated and insulted" to change their position and contrasts the conformist discourse of "successful" and "positive" social actors with ressentiment as the worldview of defective losers. Such criticism turns out to be ineffective in modern Russia. No matter how accurate its attacks may be, they cannot re-educate neither the truly "humiliated and insulted", who have nothing to lose, nor the "successful" representatives of the elites. Criticism of Russian ressentiment could have a greater effect in case of being focused on the difference between the ressentiment of the elites and the masses, but due to inherent ideological limitations, it is incapable of doing this. It remains a kind of "external", westernizing discourse, acting from the standpoint of selfevident normativity, in relation to which everything else is a deviation. In fact, it has no one to turn to within the Russian society, which over the past decades has grown tired of this kind of criticism and shows a rather high degree of unity in rejecting both those "successful people" who left Russia a long time ago and those who have left it quite recently. Therefore, in this case, it fails to achieve its goal.